2015
DOI: 10.5935/0034-7280.20150016
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal osmolaritu and ocular surface in experimental model of dry eye caused by toxicity

Abstract: The authors declare no conflict of interest. Objetivo: Descrever um modelo animal de olho seco induzido pela aplicação tópica de cloreto de benzalcônio (BAC) e avaliar marcadores de ABSTRACT RESUMOPurpose: Describe an animal model of dry induced by topical instillation of BAK and evaluate ocular surface biomarkers and histological findings. Methods: Male Wistar rats were used. Topical instillation of 0.2% BAK eyedrops twice a day during 7 days, in the right eye of each animal, while the other eye was taken as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
2
18
0
2
Order By: Relevance
“…In brief, immediately after a rising concentration of carbon dioxide resulted in death of 8- to 26-wk-old rats, ~7 by ~5-mm conjunctival specimens were excised from each eye, hemi-sectioned, positioned with the exterior surface upwards in a glass-bottom 0.75-mL recording chamber and stabilized with a harp-shaped tissue anchor (SHD26GH/10; Warner Instruments, Hamden, CT, USA). The chamber was then filled with a solution consisting of 105 mM NaCl, 15 mM NaHCO 3 , 10 Na-Hepes, 20 mM KCl, 0.5 mM CaCl 2 , 0.5 mM MgCl 2 , and 3 mM glucose; the pH was adjusted to 7.5, and a vapor pressure osmometer (Vapro 5600, Wescor, Logan, UT, USA) confirmed that osmolarity was 300 mosM, which is normosmotic for the tears of rats, rabbits, and humans [ 23 , 24 , 25 ]. Additionally of note, the K + and divalent cation concentrations, as well as the pH, reflect the values measured in normal tears of various animals and humans [ 1 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In brief, immediately after a rising concentration of carbon dioxide resulted in death of 8- to 26-wk-old rats, ~7 by ~5-mm conjunctival specimens were excised from each eye, hemi-sectioned, positioned with the exterior surface upwards in a glass-bottom 0.75-mL recording chamber and stabilized with a harp-shaped tissue anchor (SHD26GH/10; Warner Instruments, Hamden, CT, USA). The chamber was then filled with a solution consisting of 105 mM NaCl, 15 mM NaHCO 3 , 10 Na-Hepes, 20 mM KCl, 0.5 mM CaCl 2 , 0.5 mM MgCl 2 , and 3 mM glucose; the pH was adjusted to 7.5, and a vapor pressure osmometer (Vapro 5600, Wescor, Logan, UT, USA) confirmed that osmolarity was 300 mosM, which is normosmotic for the tears of rats, rabbits, and humans [ 23 , 24 , 25 ]. Additionally of note, the K + and divalent cation concentrations, as well as the pH, reflect the values measured in normal tears of various animals and humans [ 1 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dry eye injures the cornea in humans and companion animals; model animals of dry eye have been reported. [8][9][10] This disease reduces the quality of life in patients because it causes fatigue or pain of the eyes and eventually leads to low vision. Dry eye is known as a chronic disease associated with keratoconjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic dry eye associated to BAK chronic exposure has been recently recognized and is related to corneal denervation, ocular surface inflammation and corneal. [12,15].…”
Section: Introductionmentioning
confidence: 99%